Determinación físico - química de las aguas del Río Jubones en el sector de la Bocatoma del cantón El Guabo. - Delgado Salinas, Juan R. (2006)
With the purpose of knowing some characteristics of the water of the river Jubones in the Sector Bocatoma of the canton El Guabo he/she was carried out series of analysis of the compound nitrogenous (ammonia, saltpeter, and nitrates), fosfatados, chlorides, iron, calcium, magnesium, hardness, alkalinity, turbines and parameters aniónicos like environmental temperature and of the water.